A First Outlook of Sputtered FeWO4 Thin Films for Micro-Supercapacitor Electrodes. Issue 3 (16th March 2021) - Buvat, Gaëtan; Iadecola, Antonella; Blanchard, Florent; Brousse, Thierry; Roussel, Pascal; Lethien, Christophe
Abstract : The next generation of Internet of Things devices requires micro-supercapacitors operating at high voltage which is difficult to achieve using symmetrical design. Thus, their fabrication in an asymmetric configuration is mandatory. While MnO2 is well-established as positive electrode, the scarcity of existing efficient materials able to be used at the negative side drives the research towards new promising materials. Since few years, a new class of oxide materials, named multicationic oxides, were demonstrated to be attractive solutions as bulk electrodes for electrochemical capacitor. Among them, the wolframite-type FeWO4 oxide was proposed as an interesting negative electrode material for asymmetric FeWO4 /MnO2 electrochemical capacitors. The present paper reports for the first time on the successful thin film synthesis of such iron-tungstate oxide films by reactive DC magnetron sputtering, a deposition method widely used in the semiconductor industry to manufacture micro-devices. The pseudocapacitive behaviour documented at the bulk scale is preserved at the thin film level as well, and opens-up the possibility to use FeWO4 in the next generations of micro-supercapacitors.